Tea Ingredients Have Anti-coronavirus Disease 2019 (COVID-19) Targets Based on Bioinformatics Analyses and Pharmacological Effects on LPS-Stimulated Macrophages - Wang, Lei; Tao, Qing; Wang, Zhiguo; Shi, Jianfeng; Yan, Wei; Zhang, Li; Sun, Yaoxiang; Yao, Xiaoming (Frontiers in Nutrition, 2022)
Coronavirus disease 2019 (COVID-19) is a contagious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that caused millions of deaths and lacks treatment. Although several studies have focused on the major component of green tea, epigallocatechin 3-gallate (EGCG), which is efficient in preventing COVID-19, systemic analyses of the anti-COVID-19 potential of green tea remain insufficient. Here, we co-analyzed the target genes of tea ingredients and COVID-19 signature genes and found that epigallocatechin 3-acetalbehyde was capable of reversing the major molecular processes of COVID-19 (MAPK and NF-κB activation). These findings were further supported by Western blotting (WB), immunofluorescence, and quantitative polymerase chain reaction (qPCR) in LPS-stimulated macrophages. Moreover, using molecular docking analysis, we identified three tea ingredients ((-)-catechin gallate, D-(+)-cellobiose, and EGCG) that may interact with the vital SARS-CoV-2 protein, 5R84, compared with the qualified 5R84 ligand WGS. Thus, our results demonstrated that tea ingredients can treat COVID-19 by suppressing the COVID-19 signature genes and interacting with the vital SARS-CoV-2 protein.